A case of amoebic liver abscess complicated by bilhaemia and venous thrombosis. (April 2021) - Goel, Rohan; Roy, Akash; Ray, Debadrita; Chaluvashetty, Sreedhara B; De, Arka
Amoebic liver abscess is the most common extra-intestinal manifestation of amoebiasis. It usually responds well to treatment with metronidazole together with drainage, if indicated. Uncommonly, the abscess may rupture into the pleura, peritoneum or pericardium, bile duct at its hilum, or produce septic emboli. We present a patient with two rare complications: venous thrombosis and jaundice secondary to bilhaemia.